Comparison of 1550-nm nonablative fractional laser versus 755-nm picosecond laser with diffractive lens array for atrophic facial acne scars in asian skin: A prospective randomized split-face clinical study - Mao-Ying Lin; Sindy Hu; Chrang-Shi Lin; Wen-Hung Chung (Wolters Kluwer Medknow Publications, 2021)
Background: Nonablative lasers are popular alternatives for atrophic acne scar treatment in Asia. Objectives: We aimed to compare the efficacy and safety between 1550-nm nonablative fractional laser (NAFL) and 755-nm picosecond laser with diffractive lens array (DLA) in Asian patients. Methods: Twenty-three patients with atrophic acne scars received three sessions of split-face treatment with 1550-nm NAFL on one side and 755-nm picosecond laser with DLA on the other side. Sessions were applied at 8-week interval. Blinded dermatologists assessed efficacy through baseline and follow-up photographs. Results: A greater improvement in atrophic facial acne scars was observed on the 1550-nm NAFL side than on the 755-nm picosecond laser side (P < 0.05). Pain was significantly more severe on the 1550-nm NAFL side than the 755-nm picosecond laser side (P < 0.05). Adverse effects on the 1550-nm NAFL side included prolonged erythema, acneiform eruptions, superficial crusting, and postinflammatory hyperpigmentation. Only transient erythema was observed on the 755-nm picosecond laser side. Conclusion: Although the 1550-nm NAFL showed superior efficacy to the 755-nm picosecond laser with DLA for the treatment of atrophic facial acne scars, the latter was associated with fewer adverse effects and may be the best choice for those who request "little-to-no down-time" treatments.